Collective Dynamics and Alienation: An Examination of Violent Student Strikes in Kenya’s Higher Education - Kiboiy, Lelei K. (African Journal of Education,Science and Technology (AJEST), 2019)
This paper examines the role of alienation and collective dynamics in the violent student strikes that have been witnessed in Kenya’s higher education over the past three decades. In the past, student strikes have been in response to inadequate teaching, learning and accommodation facilities as well as student’s activism. This paper applies the political model and the collective dynamics approach to examine how policy processes at the institutional level and the emergence of collectives can precipitate violence in the university setting. Drawing examples from actual cases of riots in public universities in Kenya, this paper concludes by demonstrating how the policy process has often led to alienation. Bottlenecks in disciplinary process as well as breakdown in communication has led to riots. This has been compounded by the pre-disposition to the emergence of collectives whereby factors such as anonymity, diffusion of responsibility, group size, social identity, drugs and alcohol and frustration aggravate the situation by making the riots more violent.